Transcatheter aortic valve replacement with the VenusA-Pro and VenusA-Plus systems: preliminary experience in China - Li, Jie; Sun, Yinghao; Luo, Songyuan; Zheng, Shengneng; Chen, Jiaohua; Fu, Ming; Fang, Zhenfei; Wang, Yan; Li, Guang; Fan, Ruixin; Luo, Jianfang (Frontiers in Cardiovascular Medicine, 2023)
Background The outcomes of transcatheter aortic valve replacement (TAVR) employing the second-generation retrievable VenusA-Pro and VenusA-Plus delivery systems with the self-expanding VenusA-Valve have not been described yet. This study aims to report the outcomes of these two second-generation delivery systems. Methods From January 2022 to April 2023, we prospectively enrolled patients with severe aortic stenosis undergoing TAVR with VenusA-Pro from three centers across China in this first-in-man study and retrospectively identified those undergoing TAVR with VenusA-Plus. All outcomes were reported according to the Valve Academic Research Consortium 3 definition. The primary outcome was 30-day all-cause mortality. Results A total of 156 patients were included, of which 46 underwent TAVR with VenusA-Pro and 110 underwent TAVR with VenusA-Plus. The Society of Thoracic Surgeons median score was 2.1%, bicuspid anatomy prevalence rate was 55.1%, and the mean aortic root calcification volume was 693 mm3. The technical success rate was 91.7%, comparable between the VenusA-Pro and VenusA-Plus groups (87.0% vs. 93.6%, P = 0.169). The 30-day all-cause mortality was 2.6%, similar between the VenusA-Pro and VenusA-Plus groups (2.2% vs. 2.7%, P = 0.842). No myocardial infarction occurred. The incidences of stroke (0.6%), major bleeding (3.8%), major vascular complications (5.1%), acute kidney injury (9.0%), permanent pacemaker implantation (5.1%), new-onset atrial fibrillation (5.8%), and moderate-to-severe paravalvular aortic regurgitation (6.0%) were favorable and comparable between the two groups. The clinical outcomes were similar between the patients with bicuspid and tricuspid aortic valve, except that the incidence of permanent pacemaker implantation was lower in patients with bicuspid anatomy (1.2% vs. 10.6%, P = 0.010). Conclusions The 30-day outcomes of TAVR with VenusA-Pro and VenusA-Plus were favorable and comparable.